If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + 2) = 3(6x + 3) Reorder the terms: 5(2 + 4x) = 3(6x + 3) (2 * 5 + 4x * 5) = 3(6x + 3) (10 + 20x) = 3(6x + 3) Reorder the terms: 10 + 20x = 3(3 + 6x) 10 + 20x = (3 * 3 + 6x * 3) 10 + 20x = (9 + 18x) Solving 10 + 20x = 9 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 10 + 20x + -18x = 9 + 18x + -18x Combine like terms: 20x + -18x = 2x 10 + 2x = 9 + 18x + -18x Combine like terms: 18x + -18x = 0 10 + 2x = 9 + 0 10 + 2x = 9 Add '-10' to each side of the equation. 10 + -10 + 2x = 9 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = 9 + -10 2x = 9 + -10 Combine like terms: 9 + -10 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5
| 17*n=51 | | 4(2x-3)=2(5x+2) | | 36-n=15 | | 5x-2x-7x-3x=18+6-24-6 | | 4(4x+5)=6(6x-3) | | 12=g/4-3 | | y(70-20y+10)=0 | | y(70-2y+10)=0 | | (2+y)(3y-8)=0 | | y(70-2+y+10)=0 | | a*6+7=11 | | 39xn=3 | | x(70-10)=0 | | 3(5-3x)=25 | | 39/:n=3 | | 70-20+y+10=0 | | 18+-1n=10 | | -3(-3)+2(-3)-3=0 | | 34xn=34 | | 3[d+12]=8-4d | | 9(-9)-10(-9)+9=0 | | (9)9-10(9)+9=0 | | -5x+3=6x-2 | | 9+9=(5+4m) | | 39/n=3 | | x+(x*0.06)=50 | | x^3-x^2-32x+60=0 | | f(x)=tanh(7x) | | 9s-10t=2 | | y=1000X | | (16x^4)+(32x^3)-(8x^2)-24x+9=0 | | 2/5=8 |